Cluster electric spectroscopy of colloid chemical oxyhydrate systems - Sukharev, I͡U. I. (I͡Uriĭ Ivanovich); Apalikova, I. Yu (Materials science foundations, 2015)
This monograph deals with the shape of Liesegang operator and its respective phase diagrams of spontaneous surges and analyzed properties of cluster attractors. It describes the influence of pulsation noise or self-organization current of gel systems in a magnetic field on singularities of optic parameters of yttrium oxyhydrate, as well as on kinetic curves of changes in optic density of oxyhydrate systems, sorptive properties of d- and f-elements, and the structural organization of their colloids. This monograph is meant for postgraduate students, magisters, researchers, and those interested in solid-state chemistry and physics.